The Influence of Financial Literacy, Risk Aversion and Expectations on Retirement Planning and Portfolio Allocation in Malaysia - Mahdzan, N.S.; Mohd-Any, A.A.; Chan, M.K. (Gadjah Mada University, 2017)
The two objectives of this paper are to examine the effect of financial literacy, risk aversion and expectations on retirement planning; and, to investigate the effect of these antecedents on the retirement portfolio allocation. Data was collected via a self-administered questionnaire from a sample of 270 working individuals in Kuala Lumpur, Malaysia. Logistic and ordered probit regressions were employed to analyse the first and second objective, respectively. The results from the logistic regression indicate that future expectations significantly influence the probability of planning for retirement. Meanwhile, individuals with higher financial literacy and lower risk aversion are more likely to hold risky assets in their retirement portfolios. Subsequently, two-sample t-test and one-way ANOVA tests were conducted to further examine the differences in financial literacy, risk aversion and expectations, across demographic subgroups. The study contributes to the literature by holistically incorporating the behavioural aspects that affect retirement planning and by exploring an uncharted issue of retirement planning—namely, the retirement portfolio allocation.